Politik Kehutanan dalam Penegakkan Hukum Lingkungan dan Pengendalian Pengurangan Risiko Bencana - Wahyu Prawesthi (POLITIK, 2016)
AbstrakPenyelamatan bumi yang semakin panas akibat berkurangnya pohon penyerap karbondioksida dan gas rumah kaca yang banyak ditebang, sejatinya, adalah karena ulah manusia dengan dalih untuk peningkatan ekonomi dan perluasan lapangan pekerjaan bahkan perumahan liar. Padahal, upaya pengalihan fungsi hutan yang tidak sesuai dengan konsep lestari lingkungan bertentangan dengan Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup. Perubahan fungsi lahan hutan dengan merusak lingkungan hidup menjadi lahan perkebunan maupun lahan pertanian merupakan salah satu penyebab munculnya deforestasi yang menjadi isu sentral dunia, karena Indonesia menjadi salah satu negara penyebar pencemaran lingkungan melalui asap kebakaran hutan. Sebagaimana diketahui, setiap perubahan maupun pengalihan fungsi hutan, seperti penebangan pohon secara liar, merusak permukaan tanah dan membakar kayu atau hutan tersebut untuk percepatan perluasan lahan, sungguh tidak sesuai dengan Undang-Undang Nomor 41 Tahun 1999 tentang Kehutanan, termasuk pembakaran kayu hutan secara liar yang menyebabkan kebakaran juga tidak sesuai dengan Undang-Undang Nomor 24 Tahun 2007 tentang Penanggulangan Bencana. Dengan menggunakan metode yuridis normatif dan pendekatan peraturan perundang-undangan, maka, tampak dengan jelas betapa perubahan-perubahan terhadap fungsi lahan yang merusak lingkungan secara deforestasi dapat segera dihentikan dengan upaya penegakkan hukum secara maksimal melalui peraturan perundang-undangan. Kata Kunci : Politik Kehutanan, Penegakan, Hukum LingkunganAbstractSave the earth is getting warmer due to reduced trees absorbing carbon dioxide and greenhouse gases, where the trees are used to absorb carbon dioxide and parse geothermal has been cleared for the benefit and human greed itself in order to survive. And people really do not realize the importance of the forest, so that forests are used as well as a pretext for economic improvement and expansion of employment opportunities as well as good business for plantations, agriculture, illegal housing even without considering the concept of sustainable forest environment both flora and fauna. Also do not care if there is a disaster that will befall the human-caused forest diversion efforts are not in accordance with the concept of environmentally sustainable and not based on Law No. 32 of 2009 on the Protection and Management of theEnvironment. Changes in forest land with environmental damage to plantations and farmland is one cause of deforestation. Indonesian deforestation is also a central issue in the world, because Indonesia has one of the spreader environmental pollution through forest fire smoke. Therefore, any change or conversion of forest to land that is not used for the benefit of the forest itself is deforestation. Change or transfer of forest functions such as illegal logging, damage the soil surface, and burning wood or forest land for expansion acceleration, indeed it is not in accordance with Law No. 41 Year 1999 on Forestry, including the burning of forest wood wild causing a fire is also not in accordance with Law No. 24 of 2007 on Disaster Management, due to the presence of forest fires is one of the scope of the disaster response in both the regional and national levels.Of changes to land use are environmentally destructive deforestation was time to be stopped by law enforcement efforts to the maximum through legislation, which will be able to suppress the reduction of disaster risk and deforestation are not desired by our country.Keywords: Political Forestry, Enforcement, Environmental Law